Occurrence and Subtype Distribution of Blastocystis in Smallholder Dairy Cattle in Bangladesh (Journal of Science and Technology Research, 2024)
Blastocystis is a widespread protozoan known to induce digestive disorders in  humans and animals, including cattle globally. The parasite exhibits a significant  amount of genetic variability and is divided into 42 recognized subtypes (STs) in  mammals and birds. Sixteen of these subtypes are identified in cattle and 14 are  zoonotic. This study explored the distribution and genetic variations of Blastocystis  and its zoonotic potential in dairy cattle. Two hundred fresh fecal samples were  collected from smallholder dairy calves (aged